Incorporation of a complete set of deoxyadenosine and thymidine analogs suitable for the study of protein nucleic acid interactions into oligodeoxynucleotides. Application to the EcoRV restriction endonuclease and modification methylase - Newman, Patrick C; Nwosu, Victor U; Williams, David M; Cosstick, Richard; Seela, Frank; Connolly, Bernard A (Biochemistry (Easton), 1990)
A complete set of dA and T analogues designed for the study of protein DNA interactions has been prepared. These modified bases have been designed by considering the groups on the dA and T bases that are accessible to proteins when these bases are incorporated into double-helical B-DNA [Seeman, N. C., Rosenberg, J. M., & Rich, A. (1976) Proc. Natl. Acad. Sci. U.S.A. 73, 804-808]. Each of the positions on the two bases, having the potential to interact with proteins, have been subject to nondisruptive, conservative change. Typically a particular group (e.g., the 6-NH2 of dA or the 5-CH3 of T) has been replaced with a hydrogen atom. Occasionally keto groups (the 2- and 4-keto oxygen atoms of T) have been replaced with sulfur. The base set has been incorporated into the self-complementary dodecamer d(GACGATATCGTC) at the central d(ATAT) sequence. Melting temperature determination shows that the modified bases do not destabilize the double helix. Additionally, circular dichroism spectroscopy shows that almost all the altered bases have very little effect on overall oligodeoxynucleotide conformation and that most of the modified oligomers have a B-DNA type structure. d(GATATC) is the recognition sequence for the EcoRV restriction modification system. Initial rate measurements (at a single oligodeoxynucleotide concentration of 20 microM) have been carried out with both the EcoRV restriction endonuclease and modification methylase. This has enabled a preliminary identification of the groups of the dA and T bases within the d(GATATC) sequence that make important contacts to both proteins.